Degradation from the outside-in: targeting extracellular and membrane proteins for degradation through the endo-lysosomal pathway - Ahn, Green (Cell Chem Biol, 2021)
Targeted protein degradation (TPD) is a promising strategy to remove deleterious proteins for therapeutic benefit and to probe biological pathways. The past two decades have witnessed a surge in the development of technologies that rely on intracellular machinery to degrade challenging cytosolic targets. However, these TPD platforms leave the majority of extracellular and membrane proteins untouched. To enable degradation of these classes of proteins, internalizing receptors can be co-opted to traffic extracellular proteins to the lysosome. Sweeping antibodies and Seldegs use Fc receptors in conjunction with engineered antibodies to degrade soluble proteins. Recently, lysosome targeting chimeras (LYTACs) have emerged as a strategy to degrade both secreted and membrane-anchored targets. Together with other newcomer technologies including antibody-based PROTACs (AbTACs), modalities that degrade extracellular proteins have promising translational potential. This perspective will give an overview of TPD platforms that degrade proteins via outside-in approaches and focus on the recent development of LYTACs.